Open Access contribution to inclusive and participatory global knowledge societies - Babini, Dominique (CLACSO, Consejo Latinoamericano de Ciencias Sociales, 2021)
2013 World Summit on the Information Society multistakeholder review event (WSIS+10) UNESCO, Paris, 25-27 February 2013.